VISUAL ARTS COURSE ON SELF-RESPECT ON THE ACDEMIC SUCCESS SCORES, ART SELF-CONCEPT - YILDIZ, Uğur; YILMAZ, Meliha (Atlas Journal, 2020)
The aim of this study is to reveal the effect of self esteem, art self concepts and creativity on visual acuity levels of students. The research is descriptive. The universe of the study consists of 1023 ninth grade students studying in the center of Kırşehir in 2017-2018. The sample consisted of 341 ninth grade students. As a data collection tool; Pattern Application measurement tool to determine the academic achievement scores of Visual Arts Course, Torrance Creative Thought Test “Verbal A” (TYDT) to measure their creativity, Rosenberg Self-Perception Scale (RBA) for self-perceptions, Art Self-Concept Scale to determine their interest in art. Forms were used. Data were analyzed using SPSS-21 package program. As a result of the research, significant correlations were found between the Visual Arts Course academic scores and the self-esteem sub-dimension of dreaming, art self concepts and creativity levels. According to the results of the regression analysis, it was found that art self concept was more effective than creativity on students’ academic achievement scores, but self-esteem had no significant effect It was concluded that students with moderate academic achievement were more creative than students with high and low academic levels according to their placement scores.